2007
DOI: 10.1074/jbc.m700290200
|View full text |Cite
|
Sign up to set email alerts
|

Exocytotic Release of ATP from Cultured Astrocytes

Abstract: Astrocytes appear to communicate with each other as well as with neurons via ATP. However, the mechanisms of ATP release are controversial. To explore whether stimuli that increase [Ca 2؉ ] i also trigger vesicular ATP release from astrocytes, we labeled ATP-containing vesicles with the fluorescent dye quinacrine, which exhibited a significant co-localization with atrial natriuretic peptide. The confocal microscopy study revealed that quinacrine-loaded vesicles displayed mainly non-directional spontaneous mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
209
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(227 citation statements)
references
References 54 publications
17
209
0
1
Order By: Relevance
“…Live human osteosarcoma U2OS cells maintained in control conditions and stained with the ATP-sensitive fluorochrome quinacrine, which is usually employed for the detection of intracellular ATP-containing vesicles, 36 exhibit a green fluorescence that can readily be monitored by cytofluorometry. This signal is significantly reduced when U2OS cells are co-treated with 2-deoxyglucose (an inhibitor of glycolysis) and antimycin A (which blocks mitochondrial respiration at the level of complex III; Figure 1a), reflecting a significant depletion of intracellular ATP stores.…”
Section: Resultsmentioning
confidence: 99%
“…Live human osteosarcoma U2OS cells maintained in control conditions and stained with the ATP-sensitive fluorochrome quinacrine, which is usually employed for the detection of intracellular ATP-containing vesicles, 36 exhibit a green fluorescence that can readily be monitored by cytofluorometry. This signal is significantly reduced when U2OS cells are co-treated with 2-deoxyglucose (an inhibitor of glycolysis) and antimycin A (which blocks mitochondrial respiration at the level of complex III; Figure 1a), reflecting a significant depletion of intracellular ATP stores.…”
Section: Resultsmentioning
confidence: 99%
“…ATP is released from cells through various mechanisms, including exocytosis [34], maxi-anion channels [35], volumesensitive outwardly rectifying chloride channels [36], and gap-junction hemichannels [37]. Although the mechanism of release of ATP from cancer cells has not been clearly established, it is possible that the ability to release ATP is correlated with malignancy or motility of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…6). Our immunohistochemical studies with anti-mSLC17A9 antibodies indicated that mSLC17A9 protein is expressed in a population of astrocytes, suggesting involvement of this transporter in storage of ATP in ATP-secreting astrocytes (25)(26)(27). Thus, identification of SLC17A9 protein as a VNUT may reveal the molecular mechanisms behind how ATP is secreted from purinergic cells and provide a novel molecular target for the pathophysiology of purinergic signaling and its therapeutic potential (9)(10)(11).…”
Section: Slc17a9 Protein As a Vnutmentioning
confidence: 99%